Sistem Pemasaran Beras Di Kabupaten Landak, Provinsi Kalimantan Barat - Fera Wahyuni; Ratna Winandi Asmarantaka; Nia Rosiana (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
Landak regency has potential to develop rice with productivity surplus 52.296 tons. Increased production must be balanced with the right marketing system so the farmer and seller could gain better profit level. This study aims to analyze channel, function and the operational efficiency (marketing margin, farmer’s share, profit ratio) rice in Landak Regency. This study took 45 farmers respondents sample using purposive sampling method and 13 marketing agencies using snowball sampling method. Qualitative data processing used to analyze marketing channels and marketing institutions. Quantitative data processing used to analyze marketing margin, farmer’s share, and the ratio of benefits to costs. The research results showed that there are five marketing channel and four marketing institution involved. The marketing channel distinguished by the product from the farmer which is marketing channel 1, 2 and 3 the farmer selling the paddy (raw rice) and marketing channel 4 and 5 the farmer selling rice. The analysis of operational efficiency showed that marketing channel that relative efficient were channel 1 based on its ratio of benefit to cost that has value >1 (profitable). Improvement the institutional role of farmers such group transactions can help farmers receive more profitable price.